Pertanggungjawaban Direksi Terhadap Kepailitan Perseroan Terbatas Berdasarkan Undang Undang No 40 Tahun 2007 Tentang Perseroan Terbatas - Dewan Tara, Kadek Indra (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
That the Board of Directors has several duties and authorities, such as running the management of the company for the benefit of the company and in accordance with the goals of the company, within the limits determined by the articles of association and laws. In carrying out their duties, the Board of Directors is given full rights and powers with the consequence that every action and action taken by the Board of Directors will be considered and treated as actions and deeds of the company. In the event of bankruptcy in a limited liability company run by the directors. The responsibilities of directors in a limited liability company when bankruptcy occurs are not solely based on the provisions of Law Number 40 of 2007, but in company law generally known legal doctrines governing how a director is responsible to a limited liability company, if the actions of the directors it causes the bankruptcy of a company. This study discusses the legal consequences of a limited liability company experiencing bankruptcy, as well as the responsibility of the directors for the bankruptcy of a limited liability company based on law No. 40 of 2007 concerning limited liability companies and legal comparisons with Malaysia. The results obtained are that the limited liability company that is experiencing bankruptcy does not lose its rights and capabilities to enter into agreements, and its actions do not have legal consequences for its assets covered by bankruptcy. Regulations in Malaysia based on the Companies Act 1965, a director has unlimited liability in the sense that the directors still have to share in the losses suffered by the company. The responsibility of the directors extends to their personal assets.